2020
DOI: 10.3390/molecules25102366
|View full text |Cite
|
Sign up to set email alerts
|

IgGs from Human Milk Hydrolyze microRNAs

Abstract: Mother’s milk provides breast-fed infants with various nutrients, including peptides, proteins, DNA, RNA, antibodies, and other bioactive components promoting neonatal growth and protecting infants from viral and bacterial infection. The functions of many human milk components regarding the nutrition and protection of newborns may be very different compared to those of various biological fluids of healthy adults. For example, human milk contains catalytic antibodies (abzymes) with protein, lipid, and oligosacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…IgG and sIgA hydrolyzing DNA [ 59 , 148 , 151 ], RNA [ 148 , 151 ], oligonucleotides [ 148 , 150 , 151 ] and microRNA [ 157 , 158 ] were found in human milk. The presence of abzymes hydrolyzing β-casein [ 152 ] and polysaccharides [ 96 , 149 ] are also shown in the milk of healthy women.…”
Section: Catalytic Immunoglobulinsmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG and sIgA hydrolyzing DNA [ 59 , 148 , 151 ], RNA [ 148 , 151 ], oligonucleotides [ 148 , 150 , 151 ] and microRNA [ 157 , 158 ] were found in human milk. The presence of abzymes hydrolyzing β-casein [ 152 ] and polysaccharides [ 96 , 149 ] are also shown in the milk of healthy women.…”
Section: Catalytic Immunoglobulinsmentioning
confidence: 99%
“…Colonic infusion of RNase A decreased gut motility but increased bone mass; thus, Piezo1 ultimately regulates the gut peristalsis and bone homeostasis [ 171 ]. Considering our data that human milk sIgA and IgG hydrolyze RNA and microRNA [ 148 , 150 , 151 , 157 , 158 ], it can be assumed that these immunoglobulins are involved in the regulation of peristalsis and bone metabolism in newborns through the hydrolysis of fecal single-stranded RNA. In general, human milk abzymes may play an important role in protecting the newborns from different pathogens and gut homeostasis regulation.…”
Section: Catalytic Immunoglobulinsmentioning
confidence: 99%
“…It was shown that IgGs and sIgAs from the sera and milk of lactating mothers have several different catalytic activities ([ 12 , 13 , 14 , 15 , 16 , 17 ] and references therein). Methods of purification and characterization, including electrophoretic homogeneity of the IgG (150 kDa, H 2 L 2 : two light (L) and two heavy (H) chains) and sIgA (340 kDa, (H 2 L 2 ) 2 SJ: four light and four heavy chains, secretory (S) and join (J) components) preparations used in this study, were described in [ 73 , 74 ]. In addition, the relative activities (RAs) of seven individual IgGs and sIgAs from the milk of healthy lactating mothers in hydrolyzing four miRNAs (miR-9-5p, miR-137, miR-219-2-3p, and miR-219a-5p) were characterized.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the relative activities (RAs) of seven individual IgGs and sIgAs from the milk of healthy lactating mothers in hydrolyzing four miRNAs (miR-9-5p, miR-137, miR-219-2-3p, and miR-219a-5p) were characterized. Moreover, it was shown that the IgG and sIgA preparations used in this study do not contain impurities of canonical RNases [ 73 , 74 ]. In this study, we first analyzed the RAs of the same IgGs and sIgAs in the cleavage of five microRNAs: miR-148a-3p, miR-200c-3p, miR-378a-3p, miR-146b-5p, and let-7f-5p.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation